Cololejeunea tamasii (Lejeuneaceae, Marchantiophyta), a new species from Panama - Schäfer-Verwimp, Alfons (Phytotaxa, 2012)
Cololejeunea tamasii is described from Chiriqui province in western Panama. It is characterized by its small size, suborbicular to short oval leaf lobes with crenulate margins and papillose leaf cells as well as by its constantly reduced lobules of two cells.